Hubungan Antara Kepercayaan Diri (Self Confidence) Dengan Penyesuaian Sosial (Social Adjustment) Pada Remaja Kelas X Di SMA Swasta Nurul Amaliyah Tanjung Morawa - Muflih Pratama; Eryanti Novita (Universitas Medan Area, 2022)
This article or paper aims to find out the relationship between self-confidence and social adjustment of class X teenagers at nurul Amaliyah Tanjung Morawa private high school. The problem is focused on the relationship between self-confidence and social adjustment in class X adolescents at nurul Amaliyah Tanjung private high school. To approach this problem, theoretical references from Hurlock (2002) and Lauster (Ghufron and Risnawita, 2010) are used. The data was collected through the Likert scale and quantitatively analyzed. This study concluded that the results of the product moment correlation were known to have a relationship between self-confidence and social adjustment in class X adolescents at nurul amaliyah tanjung morawa private high school, where r_xy= 0.598 ; p = 0.000 0.050. the determinant coefficient (r^2) of the relationship between the free variable (X) and the bound variable (Y) is 0.358. This suggests that Social Adjustment is influenced by Self-Confidence. Self-confidence of 0.358% affects social adjustment.